PENGARUH PERENCANAAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN PT. PERMATA BAHARI MALINDONESIA - Rizky Trisna Firman Haqiqi (Manajemen Bisnis, 2017)
The purpose of this study was to describe the planning, development, and employee performance, and analyze the influence of planning and human resource development of the employee performance of PT Permata Bahari Malindonesia. analyzer used to describe human resource planning, human resource development, and employee performance is a range of scales. To analyze the influence of human resource planning and human resource development of employee performance is multiple linear regression analysis and the hypotheses test using f test and t test.The results of the analysis for the range scale for human resource planning including the very good category with the average score of 165, so it also the human resource development categories including the very good with the average score of 165 and employee performance including in the very high with the average score of 163. While the results show human resource planning has significant influence to employee performance and has significant influence to employee performance.